A novel type of amyloid‐beta plaques identified in early‐onset AD: Featured research and focused topic sessions: An update on the pathological, imaging and clinical features underlying heterogeneity across individuals with Alzheimer's disease. (7th December 2020) - Boon, Baayla D.C.; Bulk, Marjolein; Jonker, Allert J.; Popovic, Marko; Walter, Jochen; Kumar, Sathish; Natte, Remco; van der Weerd, Louise; Bouwman, Femke; Van de Berg, Wilma D.J.; Hoozemans, Jeroen J.M.; Rozemuller, Annemieke J.M.
Abstract: Background: The clinical presentation of Alzheimer's disease (AD) including age at onset, is remarkably heterogeneous. In previous research, we showed that inflammation is differently distributed between typical and atypical AD (Boon et al., 2018). In addition, distinct Aβ deposits in AD pathology are recognized. These deposits are called plaques when located in brain parenchyma or cerebral amyloid angiopathy (CAA) when located in the cerebral vessels. Recently, we described a novel Aβ plaque‐type, referred to as 'the coarse‐grained plaque'. In this study, we evaluate its clinical relevance and perform in‐depth morphological characterization. Method: The coarse‐grained plaque's presence was investigated in the frontal cortex of Aβ‐pathology‐positive cases (N=74), including non‐demented controls (n=15), early‐onset (EO)AD (n=38), and late‐onset (LO)AD (n=21), using a semi‐quantitative approach. Main plaque characteristics were compared to other well‐defined Aβ deposits; the classic cored plaque, the cotton wool plaque, and CAA. In‐depth characterization was done by studying the coarse‐grained plaque's Aβ isoform (Aβ40, Aβ42, AβN3pE, and pSer8Aβ) composition, neuroinflammatory component, and vascular association using immunohistochemistry and 3D confocal laser scanning microscopy imaging. Result: The plaque was only observed in cases with clinical symptoms, it was more prominent in EOAD (95%) than in LOAD (66%) and was associated with a homozygous ApoE4 status (Figure 1). The coarse‐grained plaque showed a multi‐cored Aβ morphology and was seen in the proximity of CAA‐affected sulci. Its predominant Aβ40 composition was distinct from other plaques, but showed similarities to that of CAA (Figure 2A). 3D imaging revealed a unique hollow Aβ40 ‐shell structure (Figure 2B) with microglia in Aβ‐devoid holes (Figure 3). Furthermore, the plaque's immunoreactivity for the CAA‐Type 1 specific marker norrin suggests – although having a different morphology ‐ a close etiological relation with CAA. Conclusion: The coarse‐grained plaque is a clinically relevant Aβ deposit as it occurs only in clinical AD and is more frequent in early‐onset cases. The plaque is strongly associated with neuroinflammatory and vascular changes. Differences in presence of coarse‐grained plaque among AD subtypes, contributes to the compiling evidence that also pathophysiology in AD is heterogeneous.